2003
DOI: 10.1097/01.brs.0000065569.76853.e9
|View full text |Cite
|
Sign up to set email alerts
|

Pain Immediately Upon Sitting Down and Relieved by Standing Up Is Often Associated With Radiologic Lumbar Instability or Marked Anterior Loss of Disc Space

Abstract: Low back pain occurring immediately on sitting down and relieved on standing up was statistically associated with instability (specificity 100%, sensitivity 31%) or marked anterior loss of disc space in flexion (specificity 87%, sensitivity 55%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…29,30 However, reliability analyses of radiologic methods measuring ROM of the spine are scarce, although often used in most of the in vivo studies dealing with this item. 14,22,[25][26][27] Boden and Wiesel 26 reported an excellent intraobserver and interobserver reproducibility when measuring lumbar ROM with the Cobb method as they found no statistical significant difference between 2 measurements, verified by a paired t test of P Ͼ 0.05. The results of the current study show that a lack of statistical significant 25 ; it is noteworthy that all Pearson PCCs were Ͼ0.700.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29,30 However, reliability analyses of radiologic methods measuring ROM of the spine are scarce, although often used in most of the in vivo studies dealing with this item. 14,22,[25][26][27] Boden and Wiesel 26 reported an excellent intraobserver and interobserver reproducibility when measuring lumbar ROM with the Cobb method as they found no statistical significant difference between 2 measurements, verified by a paired t test of P Ͼ 0.05. The results of the current study show that a lack of statistical significant 25 ; it is noteworthy that all Pearson PCCs were Ͼ0.700.…”
Section: Discussionmentioning
confidence: 99%
“…Maigne et al 22 reported acceptable 95% CIs for the evaluation of ROM and static translation in different lumbar postures using dynamic radiograph. With respect to their results, they concluded that translation is easier to measure than rotation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly none of these devices produce rigidity of a fusion, and the clinical efficacy would seem likely to be due to the fact that they prevent the spine from moving into a position where pain is experienced, (especially flexion) they certainly alter the loading patterns of the segment. The association of sitting pain (essentially flexion pain) with loading of the front of the disc is well shown in the paper by Maigne [23] where he demonstrated that patients who got pain sitting, relieved when they stood up, showed marked loss of the anterior disc space.…”
Section: Flexible Stabilizationmentioning
confidence: 88%